2011
DOI: 10.1016/j.trstmh.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-hospital care for venomous snake bite on outcome in Nigeria

Abstract: We studied pre-hospital practices of 72 consecutive snake bite victims at a hospital in north-central Nigeria. The primary outcome assessed was death or disability at hospital discharge. Victims were predominantly male farmers, and in 54 cases (75%) the snake was identified as a carpet viper (Echis ocellatus), with the remainder unidentified. Most subjects (58, 81%) attempted at least one first aid measure after the bite, including tourniquet application (53, 74%), application (15, 21%) or ingestion (10, 14%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 13 publications
1
77
0
Order By: Relevance
“…Several patient related factors, such as younger age, vomiting, increased serum creatinine, abnormal 20 min WBCT test, neurotoxic envenomation and increased severity of illness at admission,7–9 19 have been found to be associated with increased mortality and morbidity in victims of snake envenomation. Likewise, in our study, we found younger age, vomiting and haemoglobin ≤10 gm/dl at admission to be associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several patient related factors, such as younger age, vomiting, increased serum creatinine, abnormal 20 min WBCT test, neurotoxic envenomation and increased severity of illness at admission,7–9 19 have been found to be associated with increased mortality and morbidity in victims of snake envenomation. Likewise, in our study, we found younger age, vomiting and haemoglobin ≤10 gm/dl at admission to be associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that secondary bacterial infections from snakebites are related to the oral and fangs microbiota of the perpetrating snake [2026]. Besides, traditional treatment also contributes for the emergence of secondary infections, such as tourniquet use, local alternative medicines, incision and suction of the bite site [8,18,27]. These factors increase the development of expressive forms of secondary infection, which has been primarily diagnosed with identification of cellulitis or abscesses [12,13,22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ampicillin/cephalosporin/cloxacillin [14,27], ciprofloxacin [15,22] and clindamycin [36,38,39] were previously used for secondary bacterial infections resulted from snakebites, with variable effectiveness. In the Amazon, basic information about the bacterial agents responsible by the wound infection is still lacking since secondary infection diagnosis is mostly based only from clinical features without microbiological confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of traditional healing methods after a snakebite, before seeking professional treatment, is common in Bangladesh (86% by statistics) , Nigeria (81%) (Michael et al, 2011), Pakistan (75%) (Chandio et al, 2000), Kenya (68%) (Snow et al, 1994), India (74%) (Hati et al, 1992) and 61% (Inamdar et al, 2010), and Nepal (22%) (Sharma et al, 2004a), (56%) (Pandey, 2007) and (26%) (Pandey et al, 2010a). In Nepal, snakebite victims in many cases still use various dangerous and useless first aid measures.…”
Section: Introductionmentioning
confidence: 99%